2016
DOI: 10.1097/mao.0000000000000925
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Sequential Cochlear Implantation in Patients With Enlarged Vestibular Aqueduct (EVA) Syndrome

Abstract: Bilateral sequential cochlear implantation can be performed safely in patients with EVA. Audiometric outcomes are excellent and comparable to pediatric cochlear implant patients with no malformations. CSF gusher rates can be minimized by trans-round window approach. Further long-term studies are needed to identify differences within IP-EVA spectrum deformities, audiometric outcomes, and proportions of EVA patients who will need cochlear implantation for hearing rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
0
17
0
5
Order By: Relevance
“…A great diversity of clinical manifestations, in particular audiometric characteristics of hearing loss and vestibular symptoms, typically reported among patients with EVA [ 28 , 29 , 30 ], was confirmed in our cohort of 19 patients from Austria, including one patient with agenesis of the vestibular aqueduct on both sides ( Table 1 , Tables S1 and S2 ). An intraoperative gusher phenomenon of cerebro-spinal fluid during cochlea implant surgery was observed in 7 of 23 operated ears (30.4%) ( Table S1 ), an incidence that is relatively high compared to other groups [ 31 , 32 ]. However, the condition was manageable in all cases by accurate sealing during surgery without any postoperative leakage observed.…”
Section: Discussionmentioning
confidence: 99%
“…A great diversity of clinical manifestations, in particular audiometric characteristics of hearing loss and vestibular symptoms, typically reported among patients with EVA [ 28 , 29 , 30 ], was confirmed in our cohort of 19 patients from Austria, including one patient with agenesis of the vestibular aqueduct on both sides ( Table 1 , Tables S1 and S2 ). An intraoperative gusher phenomenon of cerebro-spinal fluid during cochlea implant surgery was observed in 7 of 23 operated ears (30.4%) ( Table S1 ), an incidence that is relatively high compared to other groups [ 31 , 32 ]. However, the condition was manageable in all cases by accurate sealing during surgery without any postoperative leakage observed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there has been some concern over the use of sequential cochlear implantation in LVAS patients with incomplete partition malformations. Manzoor et al (2016) found that sequential cochlear implantation can be performed safely with patients with LVAS and incomplete partition malformations and that these children do as well as their peers without these anomalies. Moreover, the recommendation to implant a child with LVAS is also mediated by cochlear implant candidacy.…”
Section: Confidence In Knowledge Of and Skills For Serving Patients Wmentioning
confidence: 88%
“…A VA diameter greater than or equal to 1.5 mm in the median point or greater than or equal to 2 mm for the operculum was defined as an EVA.A central point of 1.0–1.4 mm and 1.5 to 1.9 mm operculum were considered as borderline EVA.Less than 1.0 mm for the median point and 1.5 mm for the operculum were reported as normal VA [38, 4951]. …”
Section: Methodsmentioning
confidence: 99%
“…Less than 1.0 mm for the median point and 1.5 mm for the operculum were reported as normal VA [38, 4951]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation